Optimization of a Luteolin-Loaded TPGS/Poloxamer 407 Nanomicelle: The Effects of Copolymers, Hydration Temperature and Duration, and Freezing Temperature on Encapsulation Efficiency, Particle Size, and Solubility - Muhammad Redza, Fahmi Mod Razif; Chan, Siok Yee; Riyanto, Teguh Widodo; Chew, Yik-Ling; Masriana, Hassan; Shairyzah, Ahmad Hisham; Shamima, Abdul Rahman; Long, Chiau Ming *; Tan, Ching Siang; Lee, Siew-Keah; Liew, Kai Bin (MDPI, 2023)
Background: Luteolin is a flavonoid compound that has been widely studied for its various anti-cancer properties and sensitization to multidrug-resistant cells. However, the limited solubility and bioavailability of Lut hindered its potential clinical use. Theoretically, the combination of this compound with vitamin E TPGS and poloxamer 407 can produce a synergistic effect to enhance tumor apoptosis and P-glycoprotein inhibition. This study aimed to develop and optimize vitamin E TPGS/Poloxamer 407 micelles loaded with luteolin through investigating certain factors that can affect the encapsulation efficiency and particle size of the micelle.